Refugiados angolanos em São Paulo: entre a integração ou segregação - Haydu, Marcelo (2010)
The Angolans are the most expressive presence on the arrival of African people in Brazil, searching for refugee, coming from countries in which occurs an armed conflict. Brazil was presented at the time of Angola civil war as an alternative route for the Angolans, considering that countries that traditionally received refugees, such as United States and European countries (for example, France), closed its borders for these people. However, despite the easiness to enter the Brazilian territory, the Angolan refugees have been facing a large number of difficulties in São Paulo and have to deal with indifference and prejudice on daily basis coming from São Paulo s population. Why, after such difficulties, they remain in São Paulo? Why, during the Angola civil war, the number of Angolans that came to São Paulo was almost always increasing? Finally, as has been the integration process of these people in this city? These are some questions which, during this work, we will try to answer